2016
DOI: 10.1111/cch.12397
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the Ages & Stages Questionnaires for ages 2‐2.5: a systematic review

Abstract: Variations in age or language versions used, quality of psychometric properties and quality of papers resulted in heterogeneous evidence. It is important to consider differences in cultural and contextual factors when measuring child development using these indicators. Further research is very likely to have an important impact on the interpretation of the ASQ-3 and ASQ:SE psychometric evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 45 publications
3
52
0
1
Order By: Relevance
“…New Zealand has no comparative data pertaining to detection of developmental concerns in infants under 12 months of age. There are no other studies using the ASQ‐3 or the ASQ‐SE in this setting, and there are concerns about the validity of screening at this early age (Velikonja et al., ). Despite this, the rate of detection in this study, 51.4%, is high and concerning.…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand has no comparative data pertaining to detection of developmental concerns in infants under 12 months of age. There are no other studies using the ASQ‐3 or the ASQ‐SE in this setting, and there are concerns about the validity of screening at this early age (Velikonja et al., ). Despite this, the rate of detection in this study, 51.4%, is high and concerning.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple American Academy of Pediatrics recommendations, nationwide initiatives (e.g. Birth to Five Watch Me Thrive! [https://www.acf.hhs.gov/ecd/child-health-development/watch-me-thrive], Healthy Steps [https://www.healthysteps.org], Nurse‐Family Partnership [https://www.nursefamilypartnership.org]), and expanding statewide initiatives (e.g. Assuring Better Child Development [https://nashp.org/abcd-history/] or Help Me Grow [https://helpmegrownational.org]) have fuelled ASQ‐ and ASQ:SE‐related research.…”
Section: Discussionmentioning
confidence: 99%
“…They are feasible for use in multiple settings and take 10 to 20 minutes for parents/caregivers to complete . A previous systematic review of the ASQ focused on its psychometric properties at 2 years to 2 years 6 months of age . A narrative review focused on its use in low‐ and middle‐income countries .…”
mentioning
confidence: 99%
“…However, the age of the samples and the cutoff values applied varied between these studies. Another review by Velikonja et al (2016) concluded that the psychometric properties of the original versions of the ASQ:SE for children two to two and a half years generally exhibited good reliability, sensitivity and specificity against the CBCL comparator, whereas the adapted or translated versions of these age forms exhibited more mixed results. However, the cutoff values applied on the CBCL are not reported.…”
Section: Introductionmentioning
confidence: 99%